Moulding to Perfection: Time as a Travelator (Indian Journal of Psychology & Education, 2017)
The notion of Time Perspective divides the human experience into past, present and future. The variable of Time Perspective is of Great value to both positive psychology and also in our lives. This study intends to explore the effect of Present Time Perspective (PTP) and Future Time Perspective (FTP) on delay of gratification and level of motivation among high school students. Participants (N= 200) were drawn purposively from various schools of Delhi-NCR and a collection of STPI-22 (Stanford Time Perspective Inventory), ADOGS (Academic Delay of Gratification Scale) and Achievement Motivation Scale was administered. Results were analyzed using inferential and correlational statistics. Results reveal that FTP and delay of Gratification have a significant and Positive correlation whereas a positive and Strong relation is also observed between (PTP) and both the other variables.